Decisions under Uncertainty in Social Contexts - Holger Rau; Stephan Müller (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper theoretically and experimentally studies decision-making in risky and social environments. We explore the interdependence of individual risk attitudes and inequality aversion as two decisive behavioral determinants in such contexts. Our model and the data demonstrate that individual risk aversion is attenuated when lagging behind peers, whereas it is amplified under favorable income inequality. People's choices are also are sensitive to their degree of inequality aversion.
Keywords: C91; D03; D63; D81; 330